2009
DOI: 10.1093/hmg/ddp504
|View full text |Cite
|
Sign up to set email alerts
|

Life course variations in the associations between FTO and MC4R gene variants and body size

Abstract: The timing of associations between common genetic variants for weight or body mass index (BMI) across the life course may provide insights into the aetiology of obesity. We genotyped variants in FTO (rs9939609) and near MC4R (rs17782313) in 1240 men and 1239 women born in 1946 and participating in the MRC National Survey of Health and Development. Birth weight was recorded and height and weight were measured or self-reported repeatedly at 11 time-points between ages 2 and 53 years. Hierarchical mixed models we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

30
230
1
7

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(268 citation statements)
references
References 28 publications
30
230
1
7
Order By: Relevance
“…Although just one study found an association with obesity in this review, there are in previous studies a description of decreased response to satiety in children and adolescents when rs9939609 is present, confirmed in other studies [25][26][27][28] . As Cecil, Frayling et al also identified, rs9939609 carries an association with a higher Body Mass Index (BMI) in children and adults 29 .…”
Section: Discussionsupporting
confidence: 74%
“…Although just one study found an association with obesity in this review, there are in previous studies a description of decreased response to satiety in children and adolescents when rs9939609 is present, confirmed in other studies [25][26][27][28] . As Cecil, Frayling et al also identified, rs9939609 carries an association with a higher Body Mass Index (BMI) in children and adults 29 .…”
Section: Discussionsupporting
confidence: 74%
“…This observation agrees with former findings in mature subjects. Hardy et al (2010) described a weak association between FTO and BMI at the age of 50. Jacobsson et al (2011) suggested that the effect of FTO on corporal adiposity may decrease by age.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the effect of FTO on BMI gradually diminished in men and women with advancing age, an observation shared by others. 3,[22][23][24] Jacobsson et al found no association between FTO and BMI when they analysed a cohort of 1115 men, who were repeatedly examined each decade starting from the age of 50 years. 23 Similarly, Hardy et al reported that the association between FTO and BMI increased during childhood and adolescence, peaked at around 20 years, diminished gradually with advanced age and levelled off by the age of 53 years.…”
Section: Introductionmentioning
confidence: 99%
“…23 Similarly, Hardy et al reported that the association between FTO and BMI increased during childhood and adolescence, peaked at around 20 years, diminished gradually with advanced age and levelled off by the age of 53 years. 22 Given the age-dependent reduction of growth hormone (GH) and insulin-like growth factor-I (IGF-I), 25 we hypothesized that the risk alleles of FTO were associated with the GH-IGF-I axis. Biological evidence is based on the abundant expression of FTO in the hypothalamus and pituitary gland, both key organs for the GH-IGF-I axis and also for weight control.…”
Section: Introductionmentioning
confidence: 99%